The influence of imperfectly paired helices I and III on the catalytic activity of hammerhead ribozymes. - Zoumadakis, M (1994)
Several catalytic antisense RNAs directed against different regions of the genomic or antigenomic RNA of Sendai virus were constructed. All RNAs contained the same catalytic domain based on hammerhead ribozymes but some had deletions or mutations resulting in imperfect helices I and III. Pre-annealed substrate/ribozyme complexes were used to determine the rates of the cleavage process for the different ribozymes under single-turnover conditions. It was found that the sequence context surrounding the cleavable motif influenced the cleavage efficiencies. Deletions or mutations of nucleotides 2.1 or 15.1 and 15.2 according to the numbering system for hammerhead ribozymes of Hertel et al. destroyed catalytic activity. Deletions of nucleotide 2.2 or additional nucleotides in the helix I-forming region of the ribozyme did not destruct, but only reduced the cleavage efficiencies. Similar results were observed for a deletion of nucleotide 15.3. Simultaneous deletions within helices I and III resulted in alternative cleavage sites. The potential consequences for the specificity of the ribozyme reaction are discussed.